2011
DOI: 10.1242/jeb.060301
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of muscle maintenance costs during fiber hypertrophy in the lobster Homarus americanus: are larger muscle fibers cheaper to maintain?

Abstract: SUMMARYLarge muscle fiber size imposes constraints on muscle function while imparting no obvious advantages, making it difficult to explain why muscle fibers are among the largest cell type. Johnston and colleagues proposed the 'optimal fiber size' hypothesis, which states that some fish have large fibers that balance the need for short diffusion distances against metabolic cost savings associated with large fibers. We tested this hypothesis in hypertrophically growing fibers in the lobster Homarus americanus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…the osmo-respiratory compromise influencing fish gill size (Sardella and Brauner, 2007) and muscle fibre size (Johnston et al, 2005;Jimenez et al, 2011)] and the energetic costs of trait maintenance [e.g. the cost of maintaining large cardiac and skeletal muscle masses (e.g.…”
Section: Traits Associated With Reductions In M O2max : Stream-residmentioning
confidence: 99%
See 2 more Smart Citations
“…the osmo-respiratory compromise influencing fish gill size (Sardella and Brauner, 2007) and muscle fibre size (Johnston et al, 2005;Jimenez et al, 2011)] and the energetic costs of trait maintenance [e.g. the cost of maintaining large cardiac and skeletal muscle masses (e.g.…”
Section: Traits Associated With Reductions In M O2max : Stream-residmentioning
confidence: 99%
“…If all else is equal, smaller fibres will decrease the diffusion distance to the mitochondria compared with larger fibres , but incur higher costs from maintaining ion gradients, resulting in an energetic trade-off ['optimal fibre number hypothesis' (e.g. Johnston et al, 2005;Jimenez et al, 2011)]. We predicted that if selection for a high oxygen diffusion rate were relaxed, streamresident fish with larger fibres would have a decreased cost of maintaining ion gradients and be at a selective advantage.…”
Section: Traits Associated With Reductions In M O2max : Stream-residmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed the authors to suggest an 'optimal fibre size hypothesis', which explains the allometry of muscle fibre diameter in relation to body size through a trade-off between avoiding diffusion limitations and the need to minimize the costs of ion pumping across membranes (Johnston et al, 2004). This hypothesis has been experimentally supported for fish and crustaceans by Jimenez et al (2011Jimenez et al ( , 2013, who showed that bigger specimens have larger muscle fibres than smaller ones, and that the Na + /K + -ATPase activity as well as the energetic cost of its function is lower in larger cells because of the reduced surface area to volume ratio. An inverse relationship between cell size and animal metabolic rate was found in intraspecific studies of a few species, such as mice (Konarzewski and Ksiazėk, 2013) and fish (Maciak et al, 2011;Zhang et al, 2014).…”
Section: Metabolic Scaling At Tissue and Cellular Levelsmentioning
confidence: 99%
“…This leads to a decrease in membrane fluidity and permeability, which in turn results in reduced energy expenditure of the processes maintaining transmembrane ion gradients (e.g. Na + /K + -ATPase activity, Jimenez et al, 2011) and counteracts the futile cycling of protons through the inner mitochondrial membrane (Porter et al, 1996). Thus, changes in the fatty acid composition, and consequently in the fluidity of membranes, enhance metabolic efficiency at larger body sizes.…”
Section: Introductionmentioning
confidence: 99%